2013
DOI: 10.1080/08870446.2012.759223
|View full text |Cite
|
Sign up to set email alerts
|

How does illness severity influence depression, health satisfaction and life satisfaction in patients with cardiovascular disease? The mediating role of illness perception and self-efficacy beliefs

Abstract: Numerous empirical studies have investigated the relationships between cardiovascular diseases (CVD) and patients' psychological well-being, with a focus almost exclusively on its dark side. Very little is known on the impact of illness severity on both negative and positive indicators of patients' well-being, as well as on the psychosocial variables that may mediate this association. Aim of the study was to investigate the impact of illness severity on depression as well as on health satisfaction and life sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 76 publications
3
61
0
4
Order By: Relevance
“…The impact of illness perceptions has been studied mainly in the context of psychosocial outcomes such as coping and adjustment [6]. For example, among patients with cardiovascular disease, illness perceptions have been found to mediate the association between disease severity and various outcomes including depression [7] and health satisfaction [8]. Rimington et al [9] found that physical performance (6-min walk test) 1 year following cardiac valve replacement was predicted by preoperative levels of mood and negative illness perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of illness perceptions has been studied mainly in the context of psychosocial outcomes such as coping and adjustment [6]. For example, among patients with cardiovascular disease, illness perceptions have been found to mediate the association between disease severity and various outcomes including depression [7] and health satisfaction [8]. Rimington et al [9] found that physical performance (6-min walk test) 1 year following cardiac valve replacement was predicted by preoperative levels of mood and negative illness perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos revisados, em sua grande parte, analisavam principalmente as Karademas, Zarogiannos, & Karamvakalis, 2010;MacInnes, 2013;MacInnes, 2014;McCabe, Barnason, & Houfek, 2011;Molloy et al, 2009;Mulligan et al, 2012;Riley et al, 2012;Schroeder et al, 2012;Steca et al, 2013a;2013b), um estudo foi realizado no continente Asiático (Yan et al, 2011) Mulligan et al, 2012;Schroeder et al, 2012;Steca et al, 2013b). Um outro estudo também utilizou uma escala (Self-Efficacy Scale) para medir os fatores de risco cardíaco (Steca et al, 2013a).…”
Section: Resultsunclassified
“…Em um outro estudo, maiores crenças na duração cíclica da doença se relacionaram com níveis mais elevados de incapacidade funcional e sintomas depressivos três meses após a cirurgia (Juergens et al, 2010). Já as crenças relacionadas à cronicidade da doença estiveram associadas a maiores crenças no controle do tratamento e controle pessoal (Riley et al, 2012) e com maior crença no autocuidado e autoeficácia (Steca et al, 2013b) Houve também a falta de disposição e interesse dos participantes em responderem os questionários (Mulligan et al, 2012;Schroeder et al, 2012). No estudo de Schroeder et al (2012), segundo os autores, esse aspecto deu-se pela forma de abordagem aos pacientes e pelas implicações do seu quadro clínico no momento da abordagem.…”
Section: Resultsunclassified
“…19 Patients' health satisfaction is considered a very important outcome of cardiovascular risk reduction programs 20 and, as found by Erickson et al, 21 it is associated with fewer symptoms, better cardiac function scores, and lower perceived severity of the illness. As regards illness severity, other studies showed that it significantly affects satisfaction specifically related to health, [22][23][24] leading to hypothesize a complex and reciprocal relationship.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Previous studies showed their mediational role with respect to life satisfaction, measured at the same time of the personal control variables, and depression, both in case of cross-sectional design that in case of prospective design study. [23][24][25] In particular, we tested a model, described in detail in the following sections, in which these factors mediate the impact of illness severity on patients' health satisfaction.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%